2014
DOI: 10.1097/01.tp.0000442782.98131.7c
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Kidney Transplantation Across a Positive Complement-Dependent Cytotoxicity Crossmatch

Abstract: Despite high rates of early rejection, desensitization in living-kidney transplantation results in acceptable 5-year patient and graft survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
3
31
1
1
Order By: Relevance
“…In addition, novel B-cell targeting agents, such as Rituximab or Bortezomib, and complement inhibitors have improved the management of theses patients [36][37][38]. Five-year patient and graft survival in a group of highly sensitized recipients of kidney transplants reached 86 and 72%, respectively, with the use of a combination of agents, such as TPE, IVIG and Rituximab [35].…”
Section: Key Pointsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, novel B-cell targeting agents, such as Rituximab or Bortezomib, and complement inhibitors have improved the management of theses patients [36][37][38]. Five-year patient and graft survival in a group of highly sensitized recipients of kidney transplants reached 86 and 72%, respectively, with the use of a combination of agents, such as TPE, IVIG and Rituximab [35].…”
Section: Key Pointsmentioning
confidence: 98%
“…Although the risk of AMR is significantly higher in sensitized patients, studies in kidney transplantation have demonstrated improved survival rates in those undergoing desensitization followed by transplantation when compared with those that continue waiting for an organ on the list [32]. A combination of total plasma exchange (TPE) and intravenous immunoglobulin (IVIG) is an effective desensitization regimen in SOT with good long-term outcomes in kidney transplantation [33][34][35]. In addition, novel B-cell targeting agents, such as Rituximab or Bortezomib, and complement inhibitors have improved the management of theses patients [36][37][38].…”
Section: Key Pointsmentioning
confidence: 99%
“…Desensitization has increased transplant rates, reduced waiting times, and provided a significant survival benefit for patients with DSA compared with waiting for an HLA‐compatible transplant 8. Transplant of an HLA‐incompatible kidney after desensitization is, however, associated with an increased risk of ABMR, in both the short and longer term 4, 9…”
Section: Introductionmentioning
confidence: 99%
“…Despite these efforts, the rates of antibody-mediated rejection in sensitized patients remain significantly higher compared to non-sensitized recipients (4) (5), and there continues to be a need for better desensitization and immunosuppressive strategies.…”
Section: Introductionmentioning
confidence: 99%